1986
DOI: 10.1002/ddr.430080134
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole: From an antimycotic to a drug for prostate cancer

Abstract: The observation in a few patients that gynecomastia developed during an antifungal therapy with 200 mg ketoconazole daily set the stage for a totally new application for this drug. By administering 400 mg ketoconazole orally, every 8 hr, serum testosterone levels in or close to the castrate range were obtained within 1 day in prostate cancer patients. In addition, the adrenal androgens androstenedione and dihydroepiandrosterone were dramatically reduced. The effect was due to an interaction with cytochrome P45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…In conclusion, the results of the present study support the notion that combinations of azoles with other ergosterol biosynthesis inhibitors acting at different points of the biosynthetic pathway could be useful in the treatment of human Chagas' disease because they could allow the use of lower levels of those compounds, and particularly lower levels of ketoconazole, which has well-known toxicity problems when used at dosages of greater than 400 mg/day (2,41). This proposition is further supported by the results of our recent studies on the antiproliferative effects of combinations of ketoconazole with lovastatin, a potent inhibitor of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (1), against T. cruzi both in vitro and in vivo (45).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In conclusion, the results of the present study support the notion that combinations of azoles with other ergosterol biosynthesis inhibitors acting at different points of the biosynthetic pathway could be useful in the treatment of human Chagas' disease because they could allow the use of lower levels of those compounds, and particularly lower levels of ketoconazole, which has well-known toxicity problems when used at dosages of greater than 400 mg/day (2,41). This proposition is further supported by the results of our recent studies on the antiproliferative effects of combinations of ketoconazole with lovastatin, a potent inhibitor of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (1), against T. cruzi both in vitro and in vivo (45).…”
Section: Resultssupporting
confidence: 79%
“…Trypanosomatid protozoa such as T. cruzi and the different species of Leishmania also have a strict requirement for ergosterol and related 4-desmethyl sterols, as shown in both in vitro and in vivo studies (4-11, 17, 19, 20, 22, 26-28, 30-32, 34, 43-47). However, although success has been claimed in the treatment of human cutaneous leishmaniasis with azoles (10,47), the doses of ketoconazole reported to be effective for the prevention death from lethal T. cruzi infections in mice and for the promotion of parasitological cure (30)(31)(32)34) are far greater than those that are known to produce hepatotoxicity and to block steroid hormone synthesis in humans (2,41). We have recently found that the in vitro antiproliferative activity of ketoconazole against the epimastigote and intra-ANTIMICROB.…”
mentioning
confidence: 99%
“…We recently showed that the antiproliferative synergism of ketoconazole and terbinafine against T. cruzi observed in vitro (21,35) is also found in vivo and that this potentiating action can lead to parasitological cures in a significant proportion of treated animals (24a, 37). Thus, the results of the present work support the idea of using mevinolin to potentiate the therapeutic effects of azoles, such as ketoconazole or itraconazole, in the treatment of human Chagas' disease and, in doing so, avoiding the risks of interfering with hepatic function or testosterone production that are associated with high doses of the former (3,33). VOL.…”
Section: Discussionsupporting
confidence: 74%
“…In most cases, a compensa¬ tory increase in ACTH seems capable of overcom¬ ing the inhibition of cortisol production. Never¬ theless, symptoms suggestive of hypoadrenalism have been reported (for review see Amery et al 1986) and a systematic replacement corticosteroid therapy may be recommended. The cytochrome P-450iig also catalyzes the various steps in the biosynthetic metabolism of aldosterone, starting from 11-deoxycorticosterone (Okamoto et al 1985;Yanagibashi et al 1986).…”
mentioning
confidence: 99%